Prevalence and determinants of cigarette smoking among adolescents in Blantyre City, Malawi - Muula, A S (Tanzania Journal of Health Research, 2007)
Tobacco smoking is a major risk factor for non-communicable diseases such as ischaemic heart disease, stroke,chronic obstructive airways disease and several cancers. There is little data about the prevalence and determinants ofsmoking among adolescents in southern Africa. This study aimed to determine the prevalence and determinants of cigarettesmoking among adolescents in Blantyre City, Malawi. Cross-sectional data were obtained from school-going adolescentsin Blantyre in 2001 using the Global Youth Tobacco Survey data collection instrument. Data were analysed to determineprevalence of current and ever cigarette smoking, and predictors of smoking. The prevalence of current smoking and eversmoking were 3.0% and 15.6%, respectively. Predictors of current tobacco smoking included male gender, having friendsor parents who smoked, having been exposed to advertisements about tobacco brands on television and having seen a lotof advertisements in newspapers and magazines. School programmes that included being taught about smoking in classand a class discussion on the dangers of tobacco were not associated with reduced current smoking. Intervention programmesaiming to curb tobacco smoking among adolescents should focus on dealing also with parental smoking, peer influenceand pay special attention toward male gender. School-based programmes to prevent smoking should be evaluated as somemay have little impact in influencing current smoking status. Keywords: keyword; keyword; keyword Tanzania Health Research Bulletin Vol. 9 (1) 2007: pp. 48-53